Health Coaching Education: A Conversation With Pioneers in the Field - Snyder, Suzanne (Global Advances in Health and Medicine, 2013)
In February 2013, Global Advances in Health and Medicine (GAHMJ) interviewed eight pioneers in the field of health coaching education: Michael Arloski, PhD, PCC; Linda Bark, PhD, RN, MCC, NC-BC; Georgianna Donadio, PhD; Meg Jordan, PhD, RN; Sam Magill, MBA, MCC; Margaret Moore, MBA; Linda Smith, PA-C, MA; and Cheryl Walker, ML, MCC. This article features biographies of the participants and their perspectives on the evolution and value of health coaching education and the keys to its success.